Gesture-based Teleoperation using a Holonomic Robot - Urine, Alvaro; Perez-Gutierrez, Byron; Alves, Silas [UNESP]; IEEE (Ieee, 2012)
This work presents the development and integration of an user interface (UI) framework based on various current input devices that take advantage of our ergonomics. The purpose is to teleoperate a holonomic robot using upper member gestures and postures for studying the suitable of such interfaces when programming and interacting with a mobile robot. As performance vary from UI to UI the framework is focused to be used as a complementary industrial or didactic tool thus, changing how inexperience users tackle their first impressions when working with mobile robots while performing simple gesture-based teleoperation tasks.
Keywords: Gestures; Holonomic; Posture; User interface